PENGARUH KUALITAS LAYANAN, KEPERCAYAAN, PERSEPSI HARGA, DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN JASA TRANSPORTASI ONLINE GO-JEK DI KOTA SEMARANG - Fernanda Fitria Sundoro, 14.05.51.0032; Basiya, Robertus (Students' Journal of Economic and Management, 2018)
The competition of online-based companies related to transportation services is now starting to grow rapidly one of the start-up company that is on the rise is Go-Jek. By prioritizing the quality of services with digital forms of applications and services directly to customers, then followed by trust, price perception, and corporate image of customer satisfaction online transportation services Go-Jek. Then there is a positive and significant influence between trust on customer satisfaction. There is a positive and insignificant influence between price perceptions on customer satisfaction. There is a positive and significant influence between the company image on customer satisfaction. Model feasibility test of 0,519 significant level 0,000 <0,05 hence concluded that there is positive and significant influence between service quality (X1), trust (X2), perception of price (X3), and company image (X4) to customer satisfaction (Y) simultaneously. Go-Jek online transportation in Semarang City. Keywords: service quality, trust, price perception, corporate image and customer satisfaction.